Strategy for Developing Teaching Materials for Islamic Education Media and Technology Courses in the Digital Era - Aniza Fitri; Fathorrahman, Fathorrahman (Kasyafa: Jurnal Pendidikan Agama Islam, 2026)
In the digital era, technological advancements have transformed various aspects of life, including the field of education. Islamic Religious Education (PAI), as one of the academic disciplines taught in universities, is also required to adapt to the changing times—particularly in the development of more interactive, innovative, and technology-based teaching materials. The issue addressed in this study is how teaching material development strategies are implemented in the digital era within the Islamic education study program. This is elaborated through two main focuses:   What are the strategies for developing teaching materials for the course "Media and Technology in Islamic Religious Education (PAI)”? What are the supporting and inhibiting factors in the strategy for developing teaching materials for the course "Media and Technology in Islamic Religious Education (PAI)" in the digital era. To gain deeper insights, the researcher employed a descriptive qualitative research approach. The data sources used consist of both primary and secondary data, while the data collection techniques included interviews, observations, and documentation. Synergy between lecturers, students, and educational institutions is essential in creating a conducive digital learning ecosystem. With the support of appropriate policies, enhanced teaching staff competencies, and the effective use of technology, it is expected that the development of digital-based teaching materials can be carried out optimally and provide maximum benefits for students. The inhibiting factors include limited internet access and lack of student motivation. On the other hand, the supporting factors include the availability of media, platforms, and applications that can be utilized for learning.